Sentiment Analysis of Religious Moderation in Virtual Public Spaces during the Covid-19 Pandemic - Salsabila, Unik Hanifah; Pratiwi, Anggi; Ichsan, Yazida; Husna, Difa'ul (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
In Indonesia, the COVID-19 pandemic has resulted in the virtualization of most social and educational activities, including discourse on the dynamics of Islamic education, which is colored by contextual differences in manhaj, ideology, and religious practice. Social media has evolved into a new role as a multicultural public space that reflects the Indonesian people's religious literacy diversity. As a subsystem of national education, Islamic education plays a critical role in internalizing the Indonesian people's competencies. Religious moderation literacy will lead Indonesian people who are multicultural to a more accepting and inclusive attitude while reducing social conflicts. The purpose of this research is to ascertain public sentiment toward religious literacy in Indonesia during the 2020 Covid-19 outbreak. Twitter was chosen as the virtual public space to study in this context because, according to previous research, it is a social media platform widely used by Indonesians to discuss serious topics in education and religion. The researcher employs a type of quantitative exploration as a statistical testing technique. The data collection technique was crawling through open public data associated with Twitter's Application Programming Interface (API). This research generated findings in a word cloud labeling graph containing data on religious moderation participation. The sentiment analysis score obtained is - 0.9183, which is higher than 0.4588 on religious moderation content. The combined score is 0.565, which is higher than 0.333. the results are also contained in a sentiment analysis heat map visualization. The researchers recommend future researchers compare the ratio of religious moderation material on Islamic religious education subjects in online learning.